Evolution of the muscular system in tetrapod limbs - Tatsuya Hirasawa; Shigeru Kuratani (Zoological Letters, 2018)
Abstract While skeletal evolution has been extensively studied, the evolution of limb muscles and brachial plexus has received less attention. In this review, we focus on the tempo and mode of evolution of forelimb muscles in the vertebrate history, and on the developmental mechanisms that have affected the evolution of their morphology. Tetrapod limb muscles develop from diffuse migrating cells derived from dermomyotomes, and the limb-innervating nerves lose their segmental patterns to form the brachial plexus distally. Despite such seemingly disorganized developmental processes, limb muscle homology has been highly conserved in tetrapod evolution, with the apparent exception of the mammalian diaphragm. The limb mesenchyme of lateral plate mesoderm likely plays a pivotal role in the subdivision of the myogenic cell population into individual muscles through the formation of interstitial muscle connective tissues. Interactions with tendons and motoneuron axons are involved in the early and late phases of limb muscle morphogenesis, respectively. The mechanism underlying the recurrent generation of limb muscle homology likely resides in these developmental processes, which should be studied from an evolutionary perspective in the future.